Retratos do Paço Ducal de Vila Viçosa (séculos XVI-XIX) - Flor, Susana Varela (2021)
“Portraits of the Ducal Palace of Vila Viçosa” is the result of the research carried out by the authors on the relationship established between the House of Braganza and the art of portraiture, an artistic genre always appreciated in all times. The study of some of the still existing examples was the object of re"ection throughout the book, along with the analysis of others that came to us only by written references. It is based on the chronology of the construction of the Paço Ducal and on the most striking moments of its history. Besides, authors sought to explain how the use and possession of portraits served to affirm power during the 16th and 19th centuries in Portugal. From the portraits kept in the Paço Ducal collections, authors selected perhaps those of greater artistic and iconographic value, with particular emphasis on the magnificent pictorial set of the ceiling of the “Sala dos Duques”. From painting to tiles and from sculpture to miniature, the early modern period was privileged in the present book, the essential step for the consolidation of the highest statute of the House of Bragança in Portugal and in Europe.